Dynamic responses of an inclined FGSW beam traveled by a moving mass based on a moving mass element theory - Thom, Tran Thi; Kien, Nguyen Dinh; Anh, Le Thi Ngoc (Vietnam Journal of Mechanics, 2019)
Dynamic analysis of an inclined functionally graded sandwich (FGSW) beam traveled by a moving mass is studied. The beam is composed of a fully ceramic core and two skin layers of functionally graded material (FGM). The material properties of the FGM layers are assumed to vary in the thickness direction by a power-law function, and they are estimated by Mori-Tanaka scheme. Based on the first-order shear deformation theory, a moving mass element, taking into account the effect of inertial, Coriolis and centrifugal forces, is derived and used in combination with Newmark method to compute dynamic responses of the beam. The element using hierarchical functions to interpolate the displacements and rotation is efficient, and it is capable to give accurate dynamic responses by small number of the elements. The effects of the moving mass parameters, material distribution, layer thickness ratio and inclined angle on the dynamic behavior of the FGSW beam are examined and highlighted.